Application of peroxymonosulfate in assisting g-C3N4 / CoOOH composite photocatalyst in degrading norfloxacin
Auxiliary G-C3N4/COOOH composite optical catalyst prepared through the peroxide sulfate prepared through the water thermal method, by constructing the heterogeneous knot of G-C3N4 and COOOH, it solves the problem of non-degradation of norfloxacin and achieves high-efficiency photocatalytic catalysts Degraded effect.
Patent Information
- Application Number
- CN202411450820.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The prior art is difficult to effectively remove norfloxacin. This antibiotic is not easy to degrade and accumulates in the environment for a long time, posing a threat to human health and ecological environment.
Adopt a hydrophilic legal system preparing peroxin-sulfate auxiliary G-C3N4/CooOH composite photocatalyst, and build a heterogeneous knot of G-C3N4 and COOOH through the original growth method to improve the separation effect and electronic transfer capability of photocopy electronics-cave. Essence
It significantly improves the degradation effect of norfloxacin and achieves more efficient photocatalytic degradation capabilities. At the same time, this method is simple and easy to do, the conditions are convenient to control, and the prepared catalysts have high application prospects.
Smart Images

Figure HDA0005089068030000011 
Figure HDA0005089068030000012 
Figure HDA0005089068030000013
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photocatalytic nanomaterial preparation and relates to a method for preparing a peroxymonosulfate-assisted g-C3N4 / CoOOH composite photocatalyst for removing norfloxacin. Background Art
[0002] With the development of industrialization and pharmaceuticalization, more and more antibiotics are used to fight bacteria, and norfloxacin (NOR) is one of them. Although norfloxacin has a positive effect on fighting bacteria, it is not easy to degrade. Long-term accumulation in the environment will cause great harm to human life and health and the ecological environment, and will also cause pathogens to develop drug resistance. Therefore, the removal and treatment of norfloxacin is particularly important. Among them, photocatalytic technology has attracted widespread attention because of its green, economical and efficient characteristics. Among various advanced oxidation processes (AOPS), persulfate is particularly prominent because of its significant redox potential, wide pH range and low price. Among them, peroxymonosulfate (PMS) has attracted widespread attention due to its advantages such as being easily soluble in water, environmentally friendly and easy to activate.
[0003] Graphitic carbon nitride (g-C3N4) is a substance composed of covalently bonded carbon atoms and nitrogen atoms, arranged in a conjugated layer structure, and is a non-metallic polymer. Graphitic carbon nitride is an n-type semiconductor with a band gap of 2.7eV, good visible light absorption ability, physical and chemical stability, and a suitable electronic band structure. In addition, graphitic carbon nitride has some disadvantages, such as low photogenerated carrier migration rate and surface area. In order to improve these problems, methods such as element doping, morphology control, and heterojunction formation are usually used. Adjusting graphitic carbon nitride by these methods can greatly increase the photocatalytic performance of graphitic carbon nitride.
[0004] The present invention uses a hydrothermal method to prepare activated persulfate g-C3N4 loaded nano-CoOOH catalyst, which is different from the traditional thermal precipitation method. For example, in the patent CN202211412505.X biochar loaded nano-CoOOH catalyst, the method uses the traditional thermal precipitation method. In the process of preparing the CoOOH catalyst, the biochar is dispersed in the solution. The composite catalyst sample prepared by this method is easy to agglomerate, poorly dispersed, and the composite ratio is not high. The hydrothermal method can achieve gas-liquid coexistence in a closed environment. Liquid and gaseous water can act as a pressure transmission medium under high temperature and high pressure, so that the reactants are fully dissolved in water and the reaction is thorough. At the same time, the hydrothermal method also has the advantages of dispersing the material particle size, avoiding impurities brought by ball milling, increasing the specific surface area of the material, and enhancing the activity of the catalyst.
[0005] At present, no comparative study has been conducted on the hydrothermal method and thermal precipitation method for the preparation of peroxymonosulfate-assisted g-C3N4 / CoOOH composite photocatalysts. Summary of the invention
[0006] The technical problem to be solved by the present invention is: Based on the above problem, the present invention provides a method for preparing a peroxymonosulfate-assisted g-C3N4 / CoOOH composite photocatalyst for removing norfloxacin. The present invention prepares a peroxymonosulfate-assisted g-C3N4 / CoOOH composite photocatalyst by an in-situ growth method for solar light degradation of norfloxacin. With the introduction of g-C3N4, the separation effect of the photogenerated electron-hole pairs and the electron transfer ability of CoOOH are successfully improved, and a higher norfloxacin degradation effect is achieved.
[0007] In order to achieve the above effects, the technical solution adopted by the present invention is:
[0008] A method for preparing a peroxymonosulfate-assisted g-C3N4 / CoOOH composite photocatalyst for removing norfloxacin comprises the following steps:
[0009] (1) Preparation of g-C3N4: Weigh an appropriate amount of melamine into a crucible, place it in a tube furnace at 550°C, and calcine it in an air atmosphere at a heating rate of 5°C / min for 5 h. The calcined light yellow sample is naturally cooled to obtain carbon nitride powder.
[0010] (2) Preparation of g-C3N4 / CoOOH: Weigh Co(NO3)3·6H2O and dissolve it in deionized water, and perform ultrasonic treatment, which is called solution A. At the same time, weigh a certain amount of g-C3N4 powder and add it to solution A, and perform ultrasonic treatment at the same time. Then, add sodium hydroxide solution dropwise thereto, and mix it in a water bath at 40-60°C for 1-3 minutes, then add 30% hydrogen peroxide by mass to the mixed solution, and keep it at 40-60°C for 4-6 hours. Then, centrifuge the solution to obtain a precipitate;
[0011] Furthermore, the concentration of the sodium hydroxide solution is 0.01 g / mL, and the concentration of the cobalt nitrate solution is 0.01 to 0.02 g / mL. The volume ratio of the cobalt nitrate solution: the sodium hydroxide solution and the 30% hydrogen peroxide solution is 20:10:0.5;
[0012] Furthermore, in step (2), the mass ratio of g-C3N4 to CoOOH is 0.3 to 0.9:1, and more preferably 0.7:1.
[0013] (3) Pour the precipitate from step (2) into a reaction kettle and add ethanol solvent, reacting at 70-130° C. for 8-12 hours. Finally, centrifuge and dry the precipitate to obtain g-C3N4 / CoOOH, which is denoted as x-CN / Co (x=30%-90%), where x is the weight percentage of g-C3N4 and CoOOH.
[0014] Furthermore, the preferred reaction conditions are: reaction at 80° C. for 10 h.
[0015] The prepared g-C3N4 / CoOOH composite photocatalyst has the ability to activate peroxymonosulfate (PMS) and degrade norfloxacin.
[0016] The technical advantages of the present invention are as follows: on the one hand, by using melamine as a precursor to prepare g-C3N4 and CoOOH to construct a heterojunction, the electron transfer ability is improved, the band structure is good, and the photocatalytic degradation ability is greatly improved. On the other hand, CoOOH has an excellent ability to activate peroxymonosulfate (PMS), which is the best way to stimulate PMS to produce SO4 2- The preparation method is simple and easy, and the conditions are easy to control. The reactants are fully dissolved in water through the hydrothermal method, and the reaction is thorough. At the same time, the hydrothermal method also has the advantages of dispersing the particle size of the material, avoiding impurities brought by ball milling, increasing the specific surface area of the material, and enhancing the activity of the catalyst. And the prepared Z-type composite photocatalyst g-C3N4 / CoOOH has certain application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The present invention is further described below in conjunction with the accompanying drawings.
[0018] Figure 1 It is the X-ray diffraction pattern of g-C3N4, CoOOH and 0.7-g-C3N4 / CoOOH composite photocatalyst.
[0019] Figure 2 This is a diagram of the degradation effects of g-C3N4, CoOOH and 0.7-g-C3N4 / CoOOH composite photocatalysts.
[0020] Figure 3 This is the photocatalytic experimental cycle diagram of 0.7-g-C3N4 / CoOOH composite photocatalyst.
[0021] Figure 4 These are the scanned images of g-C3N4, CoOOH and 0.7-g-C3N4 / CoOOH composite photocatalysts.
[0022] Figure 5 The purpose is to explore the effects of different solvents and temperatures on the preparation of composite samples 0.7CN / Co.
[0023] Figure 6 The degradation effect of CN / Co composite material prepared by hydrothermal reaction using water as solvent on norfloxacin. DETAILED DESCRIPTION
[0024] The present invention will now be further described in conjunction with specific embodiments. The following embodiments are intended to further illustrate the present invention rather than to further limit the present invention.
[0025] Example 1
[0026] (1) Preparation of g-C3N4: Weigh an appropriate amount of melamine into a crucible, place it in a tube furnace at 550°C, and calcine it in an air atmosphere at a heating rate of 5°C / min for 5 h. After the calcined light yellow sample is naturally cooled, carbon nitride powder (g-C3N4) is obtained.
[0027] (2) Preparation of 0.3-g-C3N4 / CoOOH: Weigh 0.291 g Co(NO3)2·6H2O and dissolve it in 20 mL deionized water, and perform ultrasonic treatment, which is called step A; at the same time, weigh 0.027 g g-C3N4 and add it to step A for ultrasonic treatment; then weigh 0.1 g NaOH and dissolve it in 10 mL deionized water, add it dropwise to step A and place it in a water bath at 50°C; after two minutes, add 0.5 mL 30% H2O2 dropwise to the mixed solution and keep it at 50°C for 5 h, then centrifuge the solution to obtain a precipitate;
[0028] (3) The obtained precipitate was poured into a reactor and 30 mL of ethanol solvent was added, and the reaction was carried out at 80° C. for 10 h. Finally, the precipitate was centrifuged and dried. A composite photocatalyst with a g-C3N4 / CoOOH mass ratio of 0.3:1 was obtained.
[0029] Example 2
[0030] (1) Preparation of g-C3N4: Weigh an appropriate amount of melamine into a crucible, place it in a tube furnace at 550°C, and calcine it in an air atmosphere at a heating rate of 5°C / min for 5 h. The calcined light yellow sample is naturally cooled to obtain carbon nitride powder.
[0031] (2) Preparation of 0.5-g-C3N4 / CoOOH: Weigh 0.291 g Co(NO3)2·6H2O and dissolve it in 20 mL deionized water, and perform ultrasonic treatment, which is called step A; at the same time, weigh 0.045 g g-C3N4 and add it to step A for ultrasonic treatment; then weigh 0.1 g NaOH and dissolve it in 10 mL deionized water, add it dropwise to step A and keep it in a water bath at 50°C; after two minutes, add 0.5 mL 30% H2O2 dropwise to the mixed solution and keep it at 50°C for 5 hours, then centrifuge the solution to obtain a precipitate;
[0032] (3) The obtained precipitate was poured into a reactor and 30 mL of ethanol solvent was added, and the reaction was carried out at 80° C. for 10 h. Finally, the precipitate was centrifuged and dried. A composite photocatalyst with a g-C3N4 / CoOOH mass ratio of 0.5:1 was obtained.
[0033] Example 3
[0034] (1) Preparation of g-C3N4: Weigh an appropriate amount of melamine into a crucible, place it in a tube furnace at 550°C, and calcine it in an air atmosphere at a heating rate of 5°C / min for 5 h. The calcined light yellow sample is naturally cooled to obtain carbon nitride powder.
[0035] (2) Preparation of 0.7-g-C3N4 / CoOOH: Weigh 0.291 g Co(NO3)2·6H2O and dissolve it in 20 mL deionized water, and perform ultrasonic treatment, which is called step A; at the same time, weigh 0.063 g g-C3N4 and add it to step A for ultrasonic treatment; then weigh 0.1 g NaOH and dissolve it in 10 mL deionized water, add it dropwise to step A and keep it in a water bath at 50°C; after two minutes, add 0.5 mL 30% H2O2 dropwise to the mixed solution and keep it at 50°C for 5 hours, then centrifuge the solution to obtain a precipitate;
[0036] (3) The obtained precipitate was poured into a reactor and 30 mL of ethanol solvent was added, and the reaction was carried out at 80° C. for 10 h. Finally, the precipitate was centrifuged and dried. A composite photocatalyst with a g-C3N4 / CoOOH mass ratio of 0.7:1 was obtained.
[0037] Example 4
[0038] (1) Preparation of g-C3N4: Weigh an appropriate amount of melamine into a crucible, place it in a tube furnace at 550°C, and calcine it in an air atmosphere at a heating rate of 5°C / min for 5 h. The calcined light yellow sample is naturally cooled to obtain carbon nitride powder.
[0039] (2) Preparation of 0.9-g-C3N4 / CoOOH: Weigh 0.291 g Co(NO3)2·6H2O and dissolve it in 20 mL deionized water, and perform ultrasonic treatment, which is called step A; at the same time, weigh 0.081 g g-C3N4 and add it to step A for ultrasonic treatment; then weigh 0.1 g NaOH and dissolve it in 10 mL deionized water, add it dropwise to step A and keep it in a water bath at 50°C; after two minutes, add 0.5 mL 30% H2O2 to the mixed solution and keep it at 50°C for 5 hours, then centrifuge the solution to obtain a precipitate;
[0040] (3) The obtained precipitate was poured into a reactor and 30 mL of ethanol solvent was added, and the reaction was carried out at 80° C. for 10 h. Finally, the precipitate was centrifuged and dried. A composite photocatalyst with a g-C3N4 / CoOOH mass ratio of 0.9:1 was obtained.
[0041] Example 5
[0042] Compared with Example 3, Example 5 differs in that: in step (3), "the obtained precipitate is poured into a reaction kettle and 30 mL of ethanol solvent is added, and the reaction is carried out at 80°C for 10 h" is replaced by "the obtained precipitate is poured into a reaction kettle and 30 mL of ethanol is added, and the reaction is carried out at 130°C for 10 h", and the other operations are the same as Example 3.
[0043] (1) Preparation of g-C3N4: Weigh an appropriate amount of melamine into a crucible, place it in a tube furnace at 550°C, and calcine it in an air atmosphere at a heating rate of 5°C / min for 5 h. The calcined light yellow sample is naturally cooled to obtain carbon nitride powder.
[0044] (2) Preparation of 0.7-g-C3N4 / CoOOH: Weigh 0.291 g Co(NO3)3·6H2O and dissolve it in 20 mL deionized water, and perform ultrasonic treatment, which is called step A; at the same time, weigh 0.063 g g-C3N4 and add it to step A for ultrasonic treatment; then weigh 0.1 g NaOH and dissolve it in 10 mL deionized water, add it dropwise to step A and keep it in a water bath at 50°C; after two minutes, add 0.5 mL 30% H2O2 dropwise to the mixed solution and keep it at 50°C for 5 hours, then centrifuge the solution to obtain a precipitate;
[0045] (3) The obtained precipitate was poured into a reactor and 30 mL of ethanol solvent was added, and the reaction was carried out at 130° C. for 10 h. Finally, the precipitate was centrifuged and dried. A composite photocatalyst with a g-C3N4 / CoOOH mass ratio of 0.7:1 was obtained.
[0046] Comparative Example 1
[0047] The difference between Comparative Example 1 and Example 3 is that the obtained precipitate is not poured into the reactor for hydrothermal reaction.
[0048] (1) Preparation of g-C3N4: Weigh an appropriate amount of melamine into a crucible, place it in a tube furnace at 550°C, and calcine it in an air atmosphere at a heating rate of 5°C / min for 5 h. The calcined light yellow sample is naturally cooled to obtain carbon nitride powder.
[0049] (2) Preparation of 0.7-g-C3N4 / CoOOH: Weigh 0.291g Co(NO3)2·6H2O and dissolve it in 20mL deionized water, and perform ultrasonic treatment, which is called step A; at the same time, weigh 0.063g g-C3N4 and add it to step A for ultrasonic treatment, then weigh 0.1g NaOH in 10mL deionized water, add it dropwise to step A and place it in a water bath at 50°C; after two minutes, add 0.5mL 30% H2O2 to the mixed solution and keep it at 50°C for 5h, then centrifuge the solution and dry the obtained precipitate. A composite photocatalyst with a mass ratio of g-C3N4 / CoOOH of 0.7:1 is obtained.
[0050] Comparative Example 2
[0051] Compared with Example 3, Comparative Example 2 differs in that: in step (3), "the obtained precipitate is poured into a reaction kettle and 30 mL of ethanol solvent is added, and the reaction is carried out at 80°C for 10 h" is replaced by "the obtained precipitate is poured into a reaction kettle and 30 mL of water solvent is added, and the reaction is carried out at 80°C for 10 h", and the other operations are the same as Example 3.
[0052] Comparative Example 3
[0053] The difference between Comparative Example 3 and Example 3 is that the obtained precipitate is hydrothermally treated at 130° C. with water solvent, and the other operations are the same as those in Example 3.
[0054] (1) Preparation of g-C3N4: Weigh an appropriate amount of melamine into a crucible, place it in a tube furnace at 550°C, and calcine it in an air atmosphere at a heating rate of 5°C / min for 5 h. The calcined light yellow sample is naturally cooled to obtain carbon nitride powder.
[0055] (2) Preparation of 0.7-g-C3N4 / CoOOH: Weigh 0.291 g Co(NO3)2·6H2O and dissolve it in 20 mL deionized water, and perform ultrasonic treatment, which is called step A; at the same time, weigh 0.063 g g-C3N4 and add it to step A for ultrasonic treatment; then weigh 0.1 g NaOH and dissolve it in 10 mL deionized water, add it dropwise to step A and keep it in a water bath at 50°C; after two minutes, add 0.5 mL 30% H2O2 to the mixed solution and keep it at 50°C for 5 hours, then centrifuge the solution to obtain a precipitate.
[0056] (3) The obtained precipitate was poured into a reactor and 30 mL of water solvent was added, and the reaction was carried out at 130° C. for 10 h. Finally, the precipitate was centrifuged and dried. A composite photocatalyst with a mass ratio of g-C3N4 / CoOOH of 0.7:1 was obtained.
[0057] In this experiment, 20 mg PMS was added as an auxiliary oxidant after the dark reaction was completed. 10 mg of photocatalyst was used to degrade 1 L of 10 mg / L NOR (norfloxacin) aqueous solution. A 500 W xenon lamp was used as a light source to simulate sunlight. First, samples were taken every 10 minutes during the dark reaction phase, and repeated three times to determine whether adsorption equilibrium was reached. Samples were taken every 5 minutes during the light reaction phase, and repeated 4 times. Each time 3 mL of the sample was taken and filtered with a filter head. The filtered solution was measured for absorbance with a liquid ultraviolet spectrophotometer to detect the degradation rate of norfloxacin within 50 minutes.
[0058] Table 1
[0059] Example Photocatalyst Degradation rate Example 1 0.3CN / Co 81% Example 2 0.5CN / Co 68% Example 3 0.7CN / Co 97.6% Example 4 0.9CN / Co 93% Example 5 0.7CN / Co 94% <![CDATA[g-C3N4]]> 10% CoOOH 60% Comparative Example 1 0.7CN / Co 78% Comparative Example 2 0.7CN / Co 84% Comparative Example 3 0.7CN / Co 78%
[0060] Figure 1 This is the X-ray diffraction spectrum of the CN / Co composite photocatalyst prepared in Example 3 obtained by X-ray diffractometer analysis. The (100) and (002) crystal planes of g-C3N4 correspond to the two diffraction peaks of 13.1° and 27.3° respectively; the peak position of CoOOH is consistent with the standard card; in the CN / Co composite sample, the peak consistent with the pure sample can be clearly observed, indicating that the sample preparation is successful.
[0061] Figure 2 a and b are the photocatalytic degradation diagrams of the prepared CN / Co composite photocatalyst for NOR (norfloxacin) by blank control and adding PMS to assist degradation, respectively. Figure 2 It can be seen from a that without adding PMS, the catalyst has almost no degradation effect on the norfloxacin solution. Figure 2From b, it can be seen that after adding 20 mg PMS at the end of the dark reaction, the degradation effect of 0.7-CN / Co composite photocatalyst on norfloxacin reached 97.6% within 50 min, which shows that 0.7-CN / Co has a high photocatalytic degradation effect.
[0062] pass Figure 2 a It can be seen that when only PMS is added and under traditional photocatalytic conditions, the photocatalytic effect is greatly limited. Figure 2 b, on this basis, the introduction of PMS as an auxiliary active agent significantly improves the photocatalytic effect. This is because the Z-type heterojunction photocatalytic composite material prepared by the present invention accelerates the electron transfer rate and reduces the recombination efficiency of electron-hole pairs. And because CoOOH, as a transition metal hydroxide, has a good activation effect on PMS. The present invention proposes a simple method for preparing a g-C3N4-CoOOH composite catalyst, and explores the mechanism of PMS activation, providing a new possibility for PMS-assisted photocatalytic degradation.
[0063] Figure 3 This is a photocatalytic degradation cycle experiment of the 0.7-CN / Co composite photocatalyst prepared in Example 3 to degrade NOR aqueous solution. It can be seen from the figure that after five cycles, the degradation effect of the composite photocatalyst does not differ by more than 6%, indicating that the composite photocatalyst has high stability.
[0064] Figure 4 This is a scanning electron microscope (SEM) image of the g-C3N4, CoOOH, and 0.7-CN / Co composite photocatalyst prepared in Example 3. Figure 4 (a) shows that g-C3N4 presents a standard block structure; Figure 4 (b) shows that CoOOH presents blocky particles; Figure 4 In (c), it can be clearly seen that two different blocks are combined together, indicating that the sample is successfully composited.
[0065] Figure 5 The effect of different solvents and temperatures on the degradation of norfloxacin solution prepared by 0.7-CN / Co composite photocatalyst prepared in Example 3. Figure 5 It can be seen that the samples without autoclave treatment and the samples with water as solvent at 130℃ have only 78% degradation effect on norfloxacin in the same time. The samples with ethanol as solvent and autoclave treatment at 80℃ have the best photocatalytic degradation effect, which is 97%. Overall, the samples treated with ethanol as solvent are better than water, and better than 130℃ at 80℃.
[0066] Figure 6The CN / Co composite photocatalyst was prepared by hydrothermal reaction at 80°C with water as solvent after thermal precipitation reaction. It can be seen from the figure that the degradation effect of CN / Co on norfloxacin solution is different from that of the sample prepared at 80°C with ethanol as solvent. Among them, the degradation effect of 0.7CN / Co prepared with water as solvent is only 84% in the same time, while the sample prepared with ethanol as solvent has 97.6%.
Claims
1. A method for preparing a g-C3N4 / CoOOH composite photocatalyst, characterized in that: (1) Weighing cobalt nitrate and dissolving it in deionized water for ultrasonic treatment, adding g-C3N4 during the ultrasonic treatment, then dropping a sodium hydroxide solution, heating in a water bath for a period of time, dropping a hydrogen peroxide solution, continuing the hydrothermal reaction, and centrifuging to obtain a precipitate after the reaction; (2) pouring the precipitate into a reactor and adding ethanol solvent, hydrothermally reacting at 70-130° C. for 8-12 h, centrifuging and drying the precipitate to obtain a g-C3N4 / CoOOH composite photocatalyst; the mass ratio of g-C3N4 to CoOOH is 0.3-0.9:
1.
2. The method for preparing the g-C3N4 / CoOOH composite photocatalyst according to claim 1, characterized in that: The preparation method of g-C3N4 is as follows: weigh melamine, heat it to 550°C at a heating rate of 5°C / min in an air atmosphere, and calcine it for 5 hours. After calcination, cool it naturally to obtain g-C3N4.
3. The method for preparing the g-C3N4 / CoOOH composite photocatalyst according to claim 1, characterized in that: The concentration of the sodium hydroxide solution is 0.01 g / mL, and the mass concentration of the hydrogen peroxide solution is 30%.
4. The method for preparing the g-C3N4 / CoOOH composite photocatalyst according to claim 1, characterized in that: The mass ratio of g-C3N4 to CoOOH is 0.7:
1.
5. The method for preparing the g-C3N4 / CoOOH composite photocatalyst according to claim 1, characterized in that: After the sodium hydroxide solution is added dropwise in step (1), hydrogen peroxide is added dropwise after being heated in a water bath at 40-60° C. for 1-3 min, and the hydrothermal reaction is continued at 40-60° C. for 4-6 h. After the reaction, a precipitate is obtained by centrifugation.
6. The method for preparing the g-C3N4 / CoOOH composite photocatalyst according to claim 1, characterized in that: The hydrothermal condition of step (2) is 80° C. for 10 h.
7. Use of the g-C3N4 / CoOOH composite photocatalyst prepared by the method according to any one of claims 1 to 6, characterized in that: The g-C3N4 / CoOOH composite photocatalyst is used in activating peroxymonosulfate to photocatalytically degrade norfloxacin.
Citation Information
Patent Citations
Biochar-loaded nano CoOOH catalyst capable of efficiently activating persulfate and preparation method of biochar-loaded nano CoOOH catalyst
CN115888717A
Preparation method and application of carbon nitride-based catalyst for inhibiting photon-generated carrier recombination
CN117920298A